Gestión administrativa del gobierno autónomo descentralizado parroquial Eloy Alfaro del cantón Chone período 2014-2018 - Moreira García, Oscar Antonio (2019)
The present investigation was carried out with the objective of evaluating the administrative management of the Eloy Alfaro Parish Decentralized Autonomous Government 2014-2018 period for the optimization of available resources, based on scientific and legal theories that gave the research support. Analyzing the budget execution of the Parish GAD for the 2014-2018 period allowed us to know that the income allocation is not very high, which limits meeting the needs of the communities. Techniques as an interview with the president of the parish board were used to investigate the current situation of administrative management, a survey of the population sample in order to obtain the degree of satisfaction of the administration carried out in said period. The results showed the lack of teamwork within the parish GAD and budget insufficiency does not allow to meet the demand for services required by the parish; likewise, there is little or no participation of citizens in the decisions taken by the parish GAD due to ignorance of citizen participation rights. Finally, improvements to the problems found in the investigation were diagnosed through a causal analysis; the same that was socialized with the president of the GAD.